1992
DOI: 10.1104/pp.98.3.840
|View full text |Cite
|
Sign up to set email alerts
|

Gradients of Turgor, Osmotic Pressure, and Water Potential in the Cortex of the Hypocotyl of Growing Ricinus Seedlings

Abstract: To evaluate the possible role of solute transport during extension growth, water and solute relations of cortex cells of the growing hypocotyl of 5-day-old castor bean seedlings (Ricinus communis L.) were determined using the cell pressure probe.Because the osmotic pressure of individual cells (ir') was also determined, the water potential (4/) could be evaluated as well at the cell level. In the rapidly growing part of the hypocotyl of wellwatered plants, turgor increased from 0.37 megapascal in the outer to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 26 publications
(53 reference statements)
2
34
1
Order By: Relevance
“…This conclusion differs from the recent one of Meshcheryakov et al (1992), who observed 9, close to zero in the cortex of the elongating tissues of castor bean seedlings using a pressure probe. Because water clearly was being absorbed by the tissue, Meshcheryakov et al (1992) concluded that gradients probably were present but were too small to detect.…”
Section: Dlscussloncontrasting
confidence: 56%
See 2 more Smart Citations
“…This conclusion differs from the recent one of Meshcheryakov et al (1992), who observed 9, close to zero in the cortex of the elongating tissues of castor bean seedlings using a pressure probe. Because water clearly was being absorbed by the tissue, Meshcheryakov et al (1992) concluded that gradients probably were present but were too small to detect.…”
Section: Dlscussloncontrasting
confidence: 56%
“…Because water clearly was being absorbed by the tissue, Meshcheryakov et al (1992) concluded that gradients probably were present but were too small to detect. We cannot explain the small magnitude of the gradients in castor bean.…”
Section: Dlscusslonmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Fx has repeatedly been suggested as a controlling factor in stem and leaf growth (e.g. Okamoto et al 1984 Nonami & Boyer 1990;Heydt & Steudle 1991;Meshcheryakov et al 1992, Pardossi et al 1994Chazen et al 1995), no consensus has been reached on whether a Fĉ hange is able to cause a lasting regulatory growth adaptation or only a transient, and hence inconsequential, response of both turgor pressure and growth (e.g. Termaat etal.…”
Section: Introductionmentioning
confidence: 99%
“…It seems likely that the vastly different values of apoplastic solute concentrations given in the literature depend on the ohject and the method of determination (Meshcheryakov et al 1992). Canny (1995) argued that the reliability of sampling of apoplastic spaces is questionable, because the term apoplast has lost its precise meaning and begins to mean different spaces (with quite different properties) to different readers.…”
Section: The State Of the Artmentioning
confidence: 99%